Synthesis and characterization of gold nanoparticles and their toxicity in alternative methods to the use of mammals - Marcelino, Monica Yonashiro [UNESP]; Borges, Felipe Azevedo [UNESP]; Scorzoni, Liliana [UNESP]; de Lacorte Singulani, Junya [UNESP]; Garms, Bruna Cambraia [UNESP]; Niemeyer, Júlia Carina; Guerra, Nayrim Brizuela; Pegorin Brasil, Giovana Sant'Ana [UNESP]; Mussagy, Cassamo Ussemane [UNESP]; de Oliveira Carvalho, Francisco Adriano; Scontri, Mateus [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; et al. (Elsevier, 2021)
In this work we synthesize and characterize AuNPs using two chemical routes: via sodium citrate and via sodium citrate/borohydride. The cytotoxicity of AuNPs was tested by traditional in vitro assays and the in vivo toxicity was evaluated using alternative animals (Galleria mellonella and Caenorhabditis elegans). Avoidance tests with Folsomia candida were carried out to evaluate possible toxic effects in the soil ecosystem. Through Scanning Electron Microscopy and Transmission Electron Microscopy we verified the spherical shape of the AuNPs, with diameters of 34.8 ± 5.5 nm (via sodium citrate) and 7.9 ± 2.2 nm (via sodium citrate/borohydride). The hydrodynamic diameters values were compatible with those obtained microscopically, 30.1 ± 10.1 nm (method A) and 8.3 ± 2.8 nm (method B). Stability of up to 6 months was verified for AuNPs synthesized via sodium citrate, while synthesis via citrate/sodium borohydride was stable for only 1 month. The AuNPs from method A showed better efficacy in the NPs formation with higher absorbance in the plasmonic band at 523 nm, higher concentration and size, spherical shape, homogeneity and stability. The cytotoxicity of the two AuNPs exhibited a slight dose- and size-dependent behavior, with cell viability greater than 80%. The in vivo toxicity in the G. mellonella model showed a survival rate of 100% for 7 days, however, with C. elegans, the percent of survival increased as the concentration of AuNPs decreased. All concentrations of AuNPs, except for the AuNPs synthesized by the citrate pathway (1 mg/kg), showed non-avoidance responses when exposed to contaminated soil.
Keywords: Alternative animal model; Avoidance response; Gold nanoparticles; Nanotoxicity